BIBLIOTECA VIRTUAL: UMA ANÁLISE DOS FATORES ANTECEDENTES DA INTENÇÃO DE USO DOS ESTUDANTES DO ENSINO SUPERIOR - Yamanaka, Thaisa Bechelli (2015)
Several studies on the acceptance and use of information technology have been conducted by different conceptual models that seek to demonstrate the existence of factors that influence the intention and behavior of users on a particular information system. Some aspects that enhance the use of intentions can be essential for the individual to choose whether or not a particular technology. This study examined the background factors that can influence the intended use of the Virtual Library of an Institution of Higher Education. Among the conceptual models studying the adoption of information technology, it was decided in this study the use of Technology Acceptance Model (TAM) proposed by Davis (1986). In this model the external variables were also added stimulus Professor and smoker in order to expand the power of explanation of the intended use of the users in question. Through a quantitative research approach, data were collected through a survey tool to obtain 406 questionnaires responses. The results of this research confirms that the influence of various factors positioned in different dimensions provide findings relevant to the adoption of virtual library. It concludes that the Teacher Incentive positively influences Ease of Use, Perceived Usefulness and the Habit of undergraduate students on the intended use of the Virtual Library. Thus, it was found that the influence of the teacher becomes a determining factor in the use of virtual library intention, which emphasizes the importance of guidance and recommendation of teachers in the use of this technological tool. The study concluded that the perceived usefulness proved to be the factor that most influences the intention to use this technology because there is a perception that if the student will use the virtual library, you can improve your performance in studies, among others. The habit can also influence the adoption of a virtual library in parallel to perceptions about the benefits that can be obtained from the use of this technology.